Paradigma Harmoni: (Teori dan Praktik Hukum Bisnis Syariah) - saepuddin (Fikroh: (Jurnal Studi Islam), 2023)
The contemporary business landscape has witnessed a growing interest in Sharia business law, as it provides an ethical and faith-based framework for conducting economic activities. This literature review explores the concept of a "Harmony Paradigm" in the context of Sharia business law, aiming to bridge the gap between theory and practice in this field. The study begins by delving into the fundamental principles of Sharia law, emphasizing its ethical underpinnings and the significance of achieving harmony in business transactions. It then reviews the existing body of literature, encompassing both theoretical frameworks and practical applications of Sharia business law. Key aspects examined include contract formation, financial instruments, corporate governance, and dispute resolution within a Sharia-compliant framework. Furthermore, the research highlights the evolving nature of Sharia business law in response to contemporary challenges and the dynamic global business environment. It also considers the impact of technological advancements and globalization on the practice of Sharia business law. In conclusion, the Harmony Paradigm represents an innovative approach to Sharia business law, promoting ethical conduct, fairness, and social responsibility. This review contributes to a deeper understanding of the theoretical foundations and practical implications of Sharia business law, offering valuable insights for scholars, practitioners, and policymakers in the field of Islamic finance and business ethics.